Stability of Patient Social Determinants of Health With a Focus on Food Insecurity - Kevin Chagin; Ashwini R. Sehgal (SAGE Publishing, 2024)
Introduction/Objectives: Many health systems screen patients for social determinants of health and refer patients with social needs to community service organizations for assistance. However, few studies have examined how social determinants of health change over time in the same individuals. Methods: We examined patients screened by The MetroHealth System in Cleveland, Ohio for 11 social determinants of health, including food insecurity, financial strain, transportation, housing stability, utilities affordability, other housing problems, intimate partner violence, social connection, physical activity, daily stress, and digital connectivity. We determined changes in these social determinants among patients screened at baseline and again after 6 to 18 months of follow-up. We further examined correlates of changes in food insecurity, because it is a common need among our patients and leads to numerous referrals to community organizations for assistance. Results: A substantial majority of patients had no change in each social determinant. For example, among 18 038 patients screened twice for food insecurity, 13 913 (77.1%) did not screen positive for food insecurity at baseline and follow-up and 1726 (9.6%) screened positive for food insecurity at both times. A total of 1080 (6.0%) did not screen positive for food insecurity at baseline but screened positive at follow-up while 1319 (7.3%) screened positive for food insecurity at baseline but not at follow-up. Among patients screening positive for food insecurity at baseline, screening negative at follow-up was independently associated with being age ≥60 years (odds ratio [OR] = 1.46, 95% confidence interval [CI] = 1.02-2.10), not screening positive for financial strain (OR = 1.64, CI = 1.27-2.13), not screening positive for housing problems (OR = 1.65, CI = 1.28-2.13), and not screening positive for intimate partner violence (OR = 1.45, OR = 1.02-2.08). A longer duration between baseline and follow-up screening was also independently associated with not screening positive for food insecurity at follow-up. Being referred for food assistance was not associated with absence of food insecurity at follow-up (OR = 0.71, CI = 0.47-1.08). Conclusions: Most patients report no change in specific social determinants of health over 6 to 18 months. Examining changes may identify subgroups at greatest risk for persistence of adverse determinants and help to evaluate the impact of assistance efforts.